Claw trimming as a lameness management practice and the association with welfare and production in dairy cows - Sadiq, Mohammed Babatunde; Ramanoon, Siti Zubaidah; Mansor, Rozaihan; Syed Hussain, Sharifah Salmah; Shaik Mossadeq, Wan Mastura (Multidisciplinary Digital Publishing Institute, 2020)
Lameness impacts negatively on dairy cattle welfare and production. Claw trimming is a routine practice for lameness management in dairy cows. Claw trimming is often applied for the treatment of clinically lame cows especially those affected with horn lesions; however, the benefits in the area of prevention are not well understood. This issue results from a combination of paucity of data on preventive trimming and shortfalls in study designs, which limits our understanding of identifying cows that will benefit more from such intervention during lactation. Computerized claw trimming database programs have the potential of curtailing some of these issues, by providing the basis for monitoring hoof health and adjusting lameness management practices in dairy herds. This review summarizes literature findings regarding claw trimming methods, their application in lameness management, as well as associations with the welfare and production of dairy cows.